Pharmacognostical identification of Alchemilla japonica Nakai et Hara - Yun Zhu; Ningjing Zhang; Peng Li (GarVal Editorial Ltda., 2015)
Context: Alchemilla japonica is a therapeutically important medicinal plant, which is widely used in traditional medicine external application for injuries as well as orally for acute diarrhea, dysmenorrhea, and menorrhagia, among others. However, there is not a correct identification of this species and is of prime importance differentiate it from commonly available adulterants or substitutes, in fresh, dried or powdered state. There is only a small number of data of pharmacological standards for identification and authentication of A. japonica. Aims: To characterize morpho-anatomically the roots, leaves and stems of Alchemilla japonica Nakai et Hara (Rosaceae), explore and establish the micromorphology and quality control method for this plant. Methods: Pharmacognostic and phytochemical investigations were conducted in terms of macroscopic, microscopic and preliminary phytochemical parameters. Results: The transverse of root showed presence of polygonal parenchyma cells and obvious triangular intercellular space. The stele of the root was tetrarch. There was trichome in the epidermis cells of stem transverse section, but its cortex was wider than others. Xylem cells arranged in continuously cyclization. The phloem was more than ten bundles. There were many trichomes on the folicolous and palisade tissue contained cluster crystal of calcium oxalate, bundle sheath forms ring closed. The diagnostic feature of powder was cluster type of crystals of calcium oxalate. Trichomes were also observed. The main diagnostic feature of powder was Pente-like thickening cell walls of the subsidiary cells. Conclusions: The leaves, roots, and stem of A. japonica can be differentiated by macro and microscopic characters. Various pharmacognostic characters that observed in this study can help in identification and standardization of this species.